Positive Behavior Values to Improve Student Self-Efficacy: A Case Study in Islamic Boarding Schools - Naqiyah, Najlatun (Open Access Macedonian Journal of Medical Sciences, 2022)
Student self-efficacy is related to the belief of individuals doing daily activities in boarding schools. This study aims to describe the positive behavior performed by Kiai and Nyai to improve student self-efficacy. Research Methods use qualitative methods with case studies. Data is obtained by interviews, observations and documentation. Data analysis uses content analysis. The results showed that Kiai and Nyai's positive behavior could improve students' self-efficacy. Examples of Kiai and Nyai's behavior include giving positive values such as honesty, patience, gratitude, self-acceptance, and self-assessment. The increase in student self-efficacy can start with oneself solving problems encountered in school. Kiai and Nyai as role models and behaviors of Islamic values can be applied by counselors to change students in a better direction to be happy. The implication is that counselors need to set an example, strengthening students' positive values so as to increase self-efficacy